P23 Off-label use of interleukin-6 inhibitors in paediatrics: a systematic review. Issue 5 (20th April 2022) - Badshah, Hafsah; Wan, Mandy; Rashed, Asia N
Abstract : Aim: Elevated Interleukin-6 (IL-6) is associated with the pathogenesis of various chronic inflammation and autoimmune conditions. 1 Currently, only three IL-6 inhibitors, tocilizumab, siltuximab and sarilumab, are approved for a limited number of conditions in adults, and only tocilizumab is licensed in children. 2 However, off-label use of these drugs has been reported in paediatrics. This review aimed to summarise the evidence base for the off-label use of these three IL-6 inhibitors in children, the indications for off-label use, and the doses prescribed. The nature of adverse events associated with the off-label use of these drugs and the clinical effectiveness were also identified. Method: A systematic search was conducted on EMBASE, Medline, and PubMed; studies published in the English language between 2009-2020, reporting the off-label use of tocilizumab, siltuximab and sarilumab in children aged 18 years or under were included. Data screening and extraction were performed independently by two reviewers. The quality of included studies was assessed using the Newcastle-Ottawa quality assessment scale for cohort and cross-sectional studies, and the National Institutes of Health quality assessment tool for case series. The review was conducted and reported in accordance with the PRISMA guidelines for systematic reviews 3 and was registered on PROSPERO with registration number CRD42021221631. Results: In total 81 studies were included in the systematic review, with 18.5% (15/81) studies deemed of good quality, 24.7% (20/81) studies of fair quality, and 56.8% (46/81) studies of poor quality. Almost all of the studies (99%, 80/81) were on tocilizumab. Only one study investigated siltuximab and none were found for sarilumab. The total number of patients included in the identified studies was 211 (210-tocilizumab, 1 siltuximab). For tocilizumab, the most frequently reported clinical indication was the management of complications associated with hematopoietic stem cell transplantation (24.3%, 51/210) followed by its use in the treatment of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) (17.5%, 14/80). Overall, tocilizumab was prescribed for 28 unlicensed indications, and the dose varied from 4 to 12 mg/kg. Dosing frequency was reported in 98.7% (79/80) of tocilizumab studies, with 'every two weeks' prescribed most often (53.2%, 72/79). Adverse events were reported in 20.4% (43/211) of patients of which 32.6% (14/43) experienced adverse events, e.g. respiratory tract infections (n=2) and low platelet counts (n=2). The clinical outcome of the off-label use of tocilizumab was described to be successful in 55% (44/80) of studies, with reported success in the treatment of SARS-COV-2 and uveitis (13.6%, 6/44, each). The article on siltuximab reported no clinical outcomes. Conclusion: This is the first systematic review of the off-label use of IL-6 directed therapies in children. The limited data suggest that tocilizumab may be effective in a number of off-label indications, but the quality of available evidence is low and there remains the need for adequately powered and well-designed studies to support its use in clinical practice. The findings of this review should be used as a basis to inform future clinical trials in paediatrics. References: Tanaka T, Narazaki M, Kishimoto T. IL-6 in inflammation, immunity, and disease. Cold Spring Harbor Perspectives in Biology 2014;6 :a016295. Electronic medicines compendium. Summary of Product Characteristics. Available at: https://www.medicines.org.uk/emc/product/6673/smpc#gref (accessed 29 Jul 2021). Moher D, Liberati A, Tetzlaff J, et al . Preferred reporting items for systematic reviews and meta-analyses: the PRISMA statement. BMJ 2009;339 :b2535.